(untitled) (Research, Society and Development, 2020)
The objective of the present work was to determine the theoretical specific mass of buttermilk pulp at different temperatures and maturation stages and to adjust to the data obtained polynomial functions, thus evaluating their mathematical correlations. The seriguelas were classified in five different maturation stages, the pulping happened manually, being used in the experiments the peel and pulp set. The theoretical specified mass was calculated and the polynomial mathematical models were adjusted to the specific mass data of the buttermilk pulp as a function of temperature (25, 30, 35, 40, 45 and 50 °C) for each of the 5 maturation stages. For maturity stage I, there was an increase from 1035.88 to 1044.29 kg/m3; II from 1046.99 to 1055.50 kg/m3; III from 1053.95 to 1062.36 kg/m3; IV from 1062.94 to 1071.35 kg/m3; V from 1072.30 to 1080.71 kg/m3 due to the decrease in temperature. The specific mass shows a positive correlation in relation to the advance in the maturation stage of the serigraphed pulp, or the inverse in the temperature relation, being justified by the increase in the concentration in the content of soluble particles. The adjustment of the polynomial functions showed a satisfactory adequacy, however, the model with four terms shows the best adjustment with R2 equal to 1 for all levels of maturation.